Metode Pemurnian Lipase Kecambah Biji Wijen (Sesamun indicum) Menggunakan Immobilized Metal Affinity - Wiwik Sri Minarni; Supriyadi Supriyadi; Chusnul Hidayat; Lutfi Suhendra (agriTECH, 2007)
A high-density matrix was prepared by coating an alumina particle with agarose using an emulsion technique. Iminodiacetic acid was immobilized onto this matrix. Charging this matrix with copper created a useful chromatography matrix for purification of indigenous sesame sprout lipase. Butanediol diglycidyl ether (BDGE) was used as spacer arm. Factors such as, adsorption pH, BDGE concentration in matrix preparation, concentration of NaCl and imidazole were investigated. Based on both the binding capacity of matrix and the eluate adsorbed lipase, the optimum BDGE concentration and the adsorption pH were found about 40 % and 7, respectively. However, an increase in NaCl concentration in adsorption buffer from 0.5 to 1.5 M resulted in 2 times decrease in the ratio between adsorbed lipase and adsorbed total proteins. More interestingly, immobilization of Cu on this matrix was highly effective in the purification lipase, since lipase could be easily eluted from matrix using low concentration of imidazole (10 mM). Enzyme recovery and purification factor were 68% and 9.4, respectively.ABSTRAKAdsorbent matrik yang mempunyai densitas tinggi dibuat dengan melapisi permukaan partikel alumina dengan agarose. Permukaan matrik dimodifikasi dengan iminodiacetic acid (IDA) menggunakan butanediol diglycidyl ether (BDGE). Gugus karboksil pada IDA digunakan untuk mengamobilisasi Cu dan digunakan untuk memisahkan indigenous lipase dari kecambah biji wijen. Kemampuan matrik tersebut pada pemurnian lipase dievaluasi. Faktor yang dipelajari adalah pengaruh konsentrasi BDGE pada preparasi matrik, pH adsorpsi, konsentrasi NaCl dan konsentrasi imidazol. Hasil penelitian menunjukkan bahwa kondisi optimum terjadi pada perlakuan konsentrasi BDGE 40 % danpH adsorpsi 7. Kenaikan NaCl dalam buffer dari 0,5 ke 1,5 M menyebabkan penurunan perbandingan lipase teradsorpsidan total protein teradsorpsi sebesar 2 kali. Dari penelitian ini dapat disimpulkan bahwa amobilisasi Cu pada matrik efektif digunakan untuk memurnikan lipase dan lipase dapat dimurnikan dengan hasil recovery sebesar 68% dan faktor purifikasi sebesar 9,4.